Presence of extended-spectrum β-lactamases in two hospitals of Lima, Perú - Morales, José Luis (2005)
Objective: To study the presence in two hospitals of Lima of extended spectrum β-lactamases (BLEE) and to identify TEM and SHV types produced by Escherichia coli and Klebsiella pneumoniae strains. Material and Methods: The selection and confirmation of BLEE producing strains was done by antimicrobial susceptibility tests. The identification of bla TEM and bla SHV genes was achieved by polymerase chain reaction (PCR) and DNA sequencing. Results: One hundred and thirty seven Escherichia coli and 18 Klebsiella pneumoniae strains were isolated from hospitalized patients between July and September 2000. Most showed high resistance to third-generation cephalosporins and aztreonam;2,9% of all E.coli and 44,4% of all K.pneumoniae isolates were confirmed as BLEE producer strains. All BLEE producer strains were multidrug-resistant and most presented coresistance to trimethoprim/sulfamethoxazole, amikacin, gentamicin and ciprofloxacin. The blaTEM gene was found in 4 strains (3 K. pneumoniae y 1 E. coli) and blaSHV gene in 6 strains (3 K. pneumoniae y 3 E. coli). Sequencing of the corresponding genes confirmed TEM-10 and SHV-5 BLEEs. Conclusion: We determined the presence of TEM and SHV BLEE types, associated to antibiotic multiresistance.